Jungbunzlauer presents bio-based citrate plasticizers. Issue 1 (January 2018) - Unknown
Abstract : Citrate ester and biodegradable ingredients specialist Jungbunzlauer has introduced two new citrate ester plasticizers, Citrofol BI eco and Citrofol BII eco. Synthesized from natural n-butanol, produced by fermentation from renewable resources, the new grades are bio-based variants of two of the company's existing plasticizers.